2012
DOI: 10.1016/j.cell.2012.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Accumulation of Desmosterol Integrates Macrophage Lipid Metabolism and Inflammatory Responses

Abstract: Summary Inflammation and macrophage foam cells are characteristic features of atherosclerotic lesions, but the mechanisms linking cholesterol accumulation to inflammation and LXR-dependent response pathways are poorly understood. To investigate this relationship, we utilized lipidomic and transcriptomic methods to evaluate the effect of diet and LDL receptor genotype on macrophage foam cell formation within the peritoneal cavities of mice. Foam cell formation was associated with significant changes in hundreds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
502
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(549 citation statements)
references
References 45 publications
42
502
2
3
Order By: Relevance
“…The important role of adenosine in neonatal macrophages and differences in their lipid and glucose metabolism was supported by an increased expression of factors such as adenosine deaminase, 24-dehydrocholesterol reductase, and glucose-6-phosphate dehydrogenase as shown in network No.3 (37). All these factors are also known to modulate the inflammatory response [45].…”
Section: Discussionmentioning
confidence: 99%
“…The important role of adenosine in neonatal macrophages and differences in their lipid and glucose metabolism was supported by an increased expression of factors such as adenosine deaminase, 24-dehydrocholesterol reductase, and glucose-6-phosphate dehydrogenase as shown in network No.3 (37). All these factors are also known to modulate the inflammatory response [45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they occupy a distinct microenvironment relative to lipid-laden foam cell macrophages. In the plaque's necrotic core, oxidized LDL (oxLDL) is bound to scavenger receptors including CD36, SR-A/B, and LOX-1 on macrophages (163 (162). However, when HO-1-deficient macrophages are treated with oxLDL, generation of ROS is amplified and secretion of pro-inflammatory IL-6, MCP-1, and the IL-8 homologue, KC is increased (128).…”
Section: Ho-1 and Atheroprotective Macrophagesmentioning
confidence: 99%
“…The main LDL modifications related to atherosclerosis development involve lipid peroxidation 5. Transcriptional response of macrophages to exposure to oxidized (ox) LDL has been tested in cultured macrophages of different sources, with diverse results that, depending on the study, suggested predominantly proinflammatory or anti‐inflammatory effects 6, 7, 8, 9. In some cases, the outcome was significantly affected by changes in experimental variables, such as the cell type, form of LDL modification and presentation to cells, or time of exposure to the lipoproteins.…”
Section: Introductionmentioning
confidence: 99%